Reporting Observational Studies of the Use of Information Technology in the Clinical Consultation - de Lusignan, S.; Pearce, C.; Kumarapeli, P.; Stavropoulou, C.; Kushniruk, A.; Sheikh, A.; Shachak, A.; Mendis, K. (Yearbook of Medical Informatics, 2011)
To develop a classification system to improve the reporting of observational studies of the use of information technology (IT) in clinical consultations.Literature review, workshops, and development of a position statement. We grouped the important aspects for consistent reporting into a “faceted classification”; the components relevant to a particular study to be used independently.The eightfacetsof ourclassification are: (1) Theoretical and methodological approach: e.g. dramaturgical, cognitive; (2) Data collection: Type and method of observation; (3) Room layout and environment: How this affects interaction between clinician, patient and computer. (4) Initiation and Interaction: Who starts the consultation, and how the participants interact; (5) Information and knowledge utilisation: What sources of information or decision support are used or provided; (6) Timing and type of consultation variables: Standard descriptors that can be used to allow comparison of duration and description of continuous activities (e.g. speech, eye contact) and episodic ones, such as prescribing; (7) Post-consultation impact measures: Satisfaction surveys and health economic assessment based on the perceived quality of the clinician-patient interaction; and (8) Data capture, storage, and export formats: How to archive and curate data to facilitate further analysis.Adoption of this classification should make it easier to interpret research findings and facilitate the synthesis of evidence across studies. Those engaged in IT-consultation research shouldconsider adopting this reporting guide.
Keywords: Healthcare research; observation; information science; medical informatics; medical records systems; computerized